Student responsibility after using SE in gymnastics as support for the MBKM curriculum - Rahmat, Ade; Cahyadi, Ashadi; Ginanjar, Agi (Journal Sport Area, 2024)
Background Problems: Responsibility is an important part for students to study at university. In the learning process, students arrive late to take part in learning and do not complete assignments or even do not do them. By using Sport Education (SE) students are given assignments in a role to be responsible for the success of learning. SE has a strong connection to the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum with students as the center of learning. Research Objectives: The aim of this research is to find out the responsibilities of each subscale according to the student's role after using SE and to test the effect of using SE on student responsibilities. Methods: The research method uses experimentation with a one-shot case study design. The participants involved in this research were 53 students at one of the universities in the sports studies program in Indramayu who were taken using convenience sampling techniques. The research instrument used the Contextual Self-Responsibility Questionnaire for sports program students. The data analysis technique uses statistical descriptions to determine the mean and standard deviation and tests hypotheses using the one-sample t test. Finding/Results: This research provides new findings regarding student responsibilities using SE at university level, especially in Indonesia as a support for the MBKM curriculum. Conclusion: This research concludes that there is an influence after using SE on student responsibility. Further investigation is needed regarding the administration of pretests, the existence of comparison classes, and the development of instruments to facilitate all roles according to the characteristics of roles in SE.